Online peer observation in Paragraph Writing Class: A study during covid pandemic - Hasna, Fadilah Habibul; Fatimah, Sitti; Sari, Senorica Yulia (Teaching English as a Foreign Language Journal, 2025)
This study aims to examine the methods employed by lecturers in teaching a Paragraph Writing class during the COVID-19 pandemic. It also investigates their perceptions of online peer observation as a tool for professional development. Peer observation serves as a professional development tool that enhances the learning process and improves teaching practices. Using a qualitative design, the study involved two lecturers who were observed by a senior faculty member across four online sessions. Data were gathered through pre-observation meetings, classroom observations, post-observation discussions, and semi-structured interviews. Post observation discussions and feedback sessions between the observer and lecturers fostered critical thinking, idea exchange, heightened awareness of teaching performance, and collaborative efforts to achieve better student outcomes. The findings indicate that (1) lecturers should advance their pedagogical methodologies, with a particular emphasis on learning strategies and information technology competencies, (2) peer observation is perceived as a valuable collaborative learning activity that improves teaching practices through feedback, skill acquisition, and mutual collaboration, and (3) challenges such as device issues, internet connectivity, and student engagement were encountered during the online teaching. The study concludes that online peer observation contributed meaningfully to professional growth by facilitating feedback, reflective practice, and collaboration.